KEMISKINAN DALAM PERSPEKTIF ISLAM: STUDI LITERATUR TERHADAP KONSEP DAN SOLUSI EKONOMI SYARIAH - Septy Putriasih; Ichsan Iqbal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Poverty is a multidimensional problem that is still a global and national challenge, including in Indonesia, which is not only related to economic aspects, but also social and spiritual. This research aims to analyze the concept of poverty from an Islamic perspective and examine the solutions offered through sharia economics. The method used is a qualitative approach with a type of literature study, with data sources in the form of books, scientific journal articles, as well as the Al-Qur'an and relevant hadith. The data collection technique was carried out through systematic searches on scientific databases, while data analysis used the content analysis method. The research results show that in the Islamic perspective, poverty is classified into needy and needy and is seen as a problem that includes economic, social and moral aspects. The causes of poverty do not only come from economic factors, but also unequal distribution of wealth, unfair economic practices, and individual factors. Islam offers a comprehensive solution through the principles of distributional justice and sharia economic instruments such as zakat, infaq, alms and waqf which play a role in redistributing wealth and empowering the community's economy. Therefore, optimizing the management of sharia economic instruments as well as synergy between the government, sharia financial institutions and the community is needed to increase the effectiveness of sustainable poverty alleviation.